Perspectivas temporales tras el ocio serio de la juventud = Time Perspectives behind the Serious Leisure of Youth = Time perspectives besides youth's serious leisure - Codina, Nuria; Pestana Montesinos, José Vicente; Valenzuela, Rafael; Stebbins, Robert A. 1938- (2024)
Serious leisure, in both a positive and a negative sense, can take up a good part of a person's time—especially in youth. In order to deepen the knowledge of the experiences of leisure and time, this research characterizes the serious leisure of a sample of young people, specifying its relationships with time perspectives (negative / positive past, hedonistic / fatalistic present, future). Serious leisure and time perspective inventories were completed by 354 young people (186 men, 174 women) with Mage = 32.18 and SD = 4.41. The results specify the frequency and duration of serious leisure activities, different from each other according to: progress in practice, effort and perseverance —aspects correlated with time perspectives; in particular, the hedonistic present. These findings offer new knowledge by seeing how —and to what extent—, in the context of youth and the ambivalence of leisure, serious leisure is imbricated in attitudes towards time —which guide and condition the behavior of the day to day.
El ocio serio, en un sentido tanto positivo como negativo, puede ocupar buena parte del tiempo de una persona —especialmente en la juventud. Para profundizar en conocimiento de las experiencias del ocio y del tiempo, en esta investigación se caracteriza el ocio serio de una muestra de jóvenes, precisando sus relaciones con las perspectivas temporales (pasados negativo / positivo, presentes hedonista / fatalista, futuro). Cumplimentaron los inventarios de ocio serio y de perspectivas temporales 354 jóvenes (186 hombres, 174 mujeres) con edad M = 32,18 y DT = 4,41. Los resultados especifican la frecuencia y la duración de los ocios serios, diferentes entre sí según: el progreso en la práctica, el esfuerzo y la perseverancia —aspectos correlacionados con las perspectivas temporales; en particular, el presente hedonista. Estos hallazgos ofrecen un nuevo conocimiento al ver de qué manera —y hasta qué punto—, en el contexto de la juventud y de la ambivalencia del ocio, el ocio serio está imbricado en las actitudes hacia el tiempo —que orientan y condicionan el comportamiento del día a día.
Keywords: Experiencia del tiempo; Juventud; Ocio; Ocio serio; Perspectivas temporales; Tiempo